THE CHARACTERIZATION OF DANCERS PARTICIPANTS OF 28TH FESTIVAL OF DANCE IN JOINVILLE – 2010 (Fiep Bulletin - online, 2010)
This present work aims to research about the dancers who attended the 28th Festival of dance in Joinville, focusing on the investigation about dancers, with the necessity to characterize the dancer first, as it is the general aim of this research. Sample wasn't collected in the probabilistic form, but it was made by 170 dancers and students. This present work deals with direct study, data collection, so it is based on field study. For the analysis of collected information, it has been used quantity and a quality method, such research has had an explanation and descriptive form. The form used to collect information was a questionnaire with fifteen (15) questions, prepared by the researcher. The results which were found pointed that those dancers had great influence from family to start dancing and the same dancers want to stay on dance and intend to be professionals in the area of dance. This research also stated that the main qualities needed for this professionalisation, are physical aspects, dedication, like for the art and with this qualities most of interviewed people feel confident about his performance and it classifies as being good. Dancers pointed out that most of his difficulties for practicing, were related to physical, and on this difficulty they have been prejudiced, like being a male dancer is a homosexual, and the lack of recognition towards dancing as a profession, and related that physical is not adequate to the practice. Finally, dancers talked about dancing in Brazil, saying that it has been in constant change and growth. This work has been justified by its importance of studying the characterization of dance, and then identifies the weaknesses of dancers and Brazilian dance.
Keywords: festival; dancer; dance